Effectiveness of sabila (aloe vera) in the treatment of wounds in students of the educational institution of pitumama-cayhuayna- 2012 - Villavicencio Guardia, Maria (2017)
Objective. Determine the degree of effectiveness of the Aloe Vera (aloe vera) in the treatment of wounds in the students of the educational institution in Pitumama-Cayhuayna – 2012. metodos. It is an experimental, longitudinal and prospective study with 2 groups, the sample is not circumstantial type probabilistic and is comprised of 15 children for the experimental group and the control group 15. The methods used for the collection of data was direct observation, survey, structured form. Descriptive statistical data analysis was conducted using a systematic orderly description of data collected and tabulated. Descriptive statistical data analysis was conducted using the statistical test of chi square. Results. In the group in study according to degree of wound healing after the treatment with Aloe Vera (aloe vera) "is observed in the experimental group the 93% (14) cases reached a good degree of healing of the wound (differentiation and reconstitution phase) and 7% (1) case is located in the proliferative phase." In the 100% control group (15) cases found in the inflammatory phase not presenting features of a healing process. The value found for chi square (X 2) = 11,267 is greater that the value critical table = 3,841, to a level of significance of 0.05 and degrees of freedom = 1, the null hypothesis (Ho), is rejected, which means that "the application of Aloe Vera (aloe vera) in the treatment of the wounds of the skin in the experimental group favored the process of wound healing. Conclusions. It has demonstrated the effectiveness of Aloe Vera in the treatment of wounds, its healing action is due to containing in their composition, amino acids and proteins involved in the formation of the fiber collagen and vitamin C which facilitates and speeds up the healing of the wound.Key words: Aloe (aloe vera), wound.